Peluang Kejahatan Dalam Pemanfaatan E-Business - Muhammad Dimas Aldy; Rika Wulandari; Mesi Suharni Banurea; Nurbaiti Nurbaiti (Pusat Riset dan Inovasi Nasional, 2024)
Opportunities for crime in the digital business world include various forms of threats, such as system hacking, theft of personal data, financial fraud, and other criminal acts that can harm companies and damage consumer trust. Digital business is a business activity that in its implementation utilizes technology as a medium, either when creating or in a series of marketing activities. In an effort to deal with opportunities for crime in the world of e-business, companies must prioritize information security, strict policy implementation, education and training for employees, as well as partnerships with security and government agencies. This research uses a qualitative literature study method by obtaining secondary data through published journal articles with the question